Study on Preload of Bolted Connections in Pitch Bearing Based on Vibration Modal Analysis - Zhang, Hongwei; Chen, Tao; Ji, Kangkang; Zhu, Meng; Ju, Chengwei (Shock and Vibration, 2023)
In wind turbine systems, bolted connections are frequently subjected to gravitational and centrifugal loads transmitted by the blades during operation. This can lead to the attenuation of bolt preloading, resulting in bolt loosening or uneven loading, which in turn affects the service life of the generator unit. Therefore, the study of bolt preloading variations is crucial. However, there are numerous factors influencing bolt preloading, and the existing techniques struggle to precisely assess bolt preloading. This paper proposed a bolt preloading evaluation technique based on the hammer modal method. Focusing on the 42CrMo4 bolted connection of a pitch bearing, a test platform for bolt preloading assessment is constructed. Hammer modal tests are conducted under various preloading forces. By combining finite element modal analysis, the correspondence between preloading changes and the bending frequencies and modes of the bolted connection is obtained. The research illustrated that with changes in bolt preloading, variations occur in coherence, phase, and natural frequencies of frequency response functions. The fundamental correlation between bolt preloading and the second-order bending frequency can be utilized to assess changes in preloading. Furthermore, the applicability of this method has been validated, offering a reference for evaluating bolt preloading.